Development of a Spectrometric Method for Heavy Metal Analysis in Urban Environments - Mila Sari; Metha Lubis (Science Journal Get Press, 2025)
This study aims to develop more advanced and efficient spectrometric methods for heavy metal analysis in urban environments. This research uses an experimental quantitative approach to develop and optimise spectra-based analysis methods. The results showed that heavy metal concentrations in industrial area soils far exceeded environmental quality standards, with Pb reaching 128.5 mg/kg, Cd 2.4, Cr 96.3, and Hg 0.21, exceeding the set quality standards. In water samples, river water near industrial areas was highly polluted for all parameters, and Pb (0.42 and 0.008 mg/L) far exceeded the safe limits. This study shows that industrial areas have significant levels of heavy metal pollution in soil, water and air compared to residential areas. Therefore, better management of industrial effluents, development of efficient pollution monitoring and detection technologies, and implementation of environmentally friendly transport strategies are urgently needed to mitigate the risks of pollution to human health and the environment.